Post-cracking ductility of fibre reinforced concrete linings in combined bending and compression - Gilbert, Raymond Ian; Bernard, Erik Stefan (Tunnelling and underground space technology, 2018)
It is often assumed that the post-crack ductility of Fibre Reinforced Concrete (FRC) and Shotcrete (FRS) is wholly defined by the result obtained in a standard flexural performance test such as ASTM C1609/C1609M or EN14651. However, the results revealed by these tests are only valid for the case of pure bending and do not incorporate the effects induced by the possible presence of an axial force within a member. A compressive axial force will substantially change the distribution of stress across a section subject to bending, and this will delay cracking, control the propagation of cracks when they occur and increase deformability, and hence ductility. The current investigation examines how an axial compressive stress changes the ductility of FRC and FRS tunnel linings, giving rise to post-crack strain hardening flexural behaviour in linings that otherwise exhibit strain-softening behaviour in standard flexural tests. The outcome has significant implications with respect to design, because enhanced ductility can thereby be exploited for moment re-distribution at ultimate load even for relatively economical levels of fibre reinforcement in concrete tunnel linings.